1971
DOI: 10.1042/bj1250635
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation in Bacillus subtilis. Effect of medium on the form of chromosome replication and on initiation to sporulation in Bacillus subtilis

Abstract: Thymine-requiring mutants of Bacillus subtilis and mutants that are temperature-sensitive for initiation of chromosome replication have been used to study the relationship between sporulation and chromosome formation. The DNA synthesis that normally occurs when cells are transferred to sporulation medium is essential for spore induction. This is shown by the fact that thymine-starved cells are unable to form spores and are unable to perform even the earlier steps of sporulation, such as septum formation or syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 11 publications
6
28
0
Order By: Relevance
“…In contrast, if the cell enters the sporulation program with more than 2 chromosomal copies, it may produce spores with multiple chromosomes or with twin spores, with one spore located at each cell pole (426). To avoid these outcomes, B. subtilis couples the process of sporulation to DNA replication (234,235). Such coupling provides a brief window during the cell cycle in which sporulation can be initiated.…”
Section: Coupling Development To Dna Replicationmentioning
confidence: 99%
“…In contrast, if the cell enters the sporulation program with more than 2 chromosomal copies, it may produce spores with multiple chromosomes or with twin spores, with one spore located at each cell pole (426). To avoid these outcomes, B. subtilis couples the process of sporulation to DNA replication (234,235). Such coupling provides a brief window during the cell cycle in which sporulation can be initiated.…”
Section: Coupling Development To Dna Replicationmentioning
confidence: 99%
“…The experiments of Mandelstam et al (1971) established a relationship between DNA replication and induction of sporulation in Bacillus subtilis. They showed that thymine deprivation in thymine auxotrophs resulted in inhibition of sporulation and of the associated biochemical events such as production of extracellular proteases, ribonuclease and alkaline phosphatase.…”
Section: Introductionmentioning
confidence: 99%
“…During transformation of B. subtilis a single strand of donor DNA integrates into the recipient chromosome, forming a heteroduplex (Dubnau, 1976). For spore formation there is an obligatory period of DNA synthesis after the start of sporulation in which most of the chromosome needs to be replicated (Mandelstam et al, 1971;Dunn et al, 1978). This replication is completed before formation of the asymmetrically sited spore division septum (Ryter & Aubert, 1969).…”
Section: Introductionmentioning
confidence: 99%